La familia y su incidencia en el desarrollo socio-afectivo de los niños y niñas de primer año de educación general básica del jardín fiscal mixto Lucía Franco de Castro de la provincia de Pichincha, período lectivo 2013-2014, lineamientos propositivos - Hernandez Villalva, Luz Maria (2014)
This thesis refers to “FAMILY AND ITS IMPACT ON SOCIO-EMOTIONAL DEVELOPMENT OF CHILDREN OF FIRST YEAR BASIC EDUCATION GARDEN GENERAL JOINT FISCAL” FRANCO DE LUCÍA CASTRO “PICHINCHA PROVINCE, 2013-2014 PERIOD LECTIVO, GUIDELINES proactive.” The general objective was: To analyze whether the family affects the Socio- Affective Development of children’s first year of Basic General Education attending the Joint Fiscal Garden "Lucía Franco de Castro”, in the province of Pichincha. The methods used for the preparation of this research work were: Scientist, Inductive, Deductive, Analytic, Synthetic, Descriptive, Statistical Model, the techniques used were: Survey applied to Parent to establish the Family Organization children First Year of Basic General Education attending the Joint Fiscal Garden "Lucía Franco de Castro " and the application of the test applied to Ebbe Leon Gross Parent to determine the Socio- Affective Development of children. In the implementation of the survey Parent concludes that 70% of respondents said that their family is organized by Father, Mother and Child, that is a nuclear family, 17% by a parent and child, which corresponds to a Single parent families, and 13% for Father, Mother , sons, uncles, cousins, grandparents, which corresponds to an extended family. From the test results Ebbe León Gross, 65 % of boys and girls investigated obtained from zero to five negative responses so manifest a Very Satisfactory Socio- Affective Development, 20% scored between five to fifteen negative responses equivalent to Satisfactory and 15% received more than 15 negative responses equivalent to Unsatisfactory.